Models of high-level computation - Arellanes, Damian (Frontiers in Computer Science, 2025)
Classical models of computation are useful for understanding computability in the small; however, they fall short when it comes to analyzing large-scale, complex computations. To address this gap, theoretical computer science has witnessed the emergence of several formalisms that attempt to raise the level of abstraction with the aim of describing not only a single computing device but interactions among a collection of them. In this paper, we unify such formalisms under a common framework, which we refer to as Models of High-Level Computation. Our aim is to offer an accessible overview of these models.